Medicine Availability and Prescribing Policy for Non-Communicable Diseases in the Western Balkan Countries - Pekez-Pavlisko, Tanja; Racic, Maja; Kusmuk, Srebrenka (Frontiers in Public Health, 2017)
Background During the transition processes, the Western Balkan countries were affected by conflicts and transition-related changes. Life expectancy in these countries is lower, while the mortality from non-communicable diseases (NCDs) is higher in comparison with western and northern parts of Europe. The primary aim of this study was to analyze the treatment possibilities for the most common NCDs in the Western Balkan countries. The secondary aim was to understand and compare the policies regarding prescribing-related competencies of family physicians. Methods In June and July 2017, a document analysis was performed of national positive medicines lists, strategic documents, and clinical guidelines for the treatment of the most frequent NCDs; arterial hypertension, diabetes, hyperlipidemia, asthma, and chronic obstructive pulmonary disease (COPD). All text phrases that referred to medicines prescribing were extracted and sorted into following domains: medicine availability, prescribing policy, and medication prescribing-related competencies. Results Possibilities for treatment of arterial hypertension, diabetes, hyperlipidemia, asthma, and COPD vary across the Western Balkan countries. This variance is reflected in the number of registered medicines, number of parallels, and number of different combinations, as well as restrictions placed on family physicians in prescribing insulin, inhaled corticosteroids, statins and angiotensin II receptor blockers (ARBs), without consultant’s recommendation. Conclusion Western Balkan countries are capable of providing essential medicines for the treatment of NCDs, with full or partial reimbursement. There are some exceptions, related to statins, newer generation of oral antidiabetic agents and some of the antihypertensive combinations. Prescribing-related competences of family physicians are limited. However, this practice is not compliant to the practices of family medicine, its principles and primary care structures, and may potentially result in increased health-care financial ramifications to both the system and patients due to frequent referrals to the specialists.